P385 Risk-benefit assessment of IBD drugs: a physicians and patients survey. (30th January 2023) - D'Amico, F; Caron, B; Vieujean, S; Peyrin-Biroulet, L; Danese, S
Abstract: Background: Treatment choices for patients with inflammatory bowel disease (IBD) are based on the balance between risks and benefits. To date, there are no globally accepted methods for assessing the risk-benefit ratio. Our aim was to compare the perspectives of patients and physicians in evaluating the risks and benefits before initiating therapy for IBD. Methods: An anonymous survey was conducted between March and August 2022. Multiple choice questions, similar for physicians and patients, were formulated. The questionnaire was developed in English and was later translated in Italian and French by native speakers. All patients with a confirmed diagnosis of IBD who were followed up at the IRCCS San Raffaele Hospital (Italy), Nancy University Hospital (France), and University Hospital CHU of Liège (Belgium) were invited to participate. All physicians who attended an IBDscope webinar were invited to participate by email. Results: In total, 367 patients and 146 physicians participated in the survey from 34 countries worldwide (Tables 1 and 2). For most patients (71.4%) and physicians (89.0%), efficacy and safety were equally important in choosing a therapy. Clinical improvement and clinical remission were the most relevant outcomes for patients (90.9 and 88.4 Likert scales), while clinical remission and endoscopic remission were for physicians (90.0 and 87.6 Likert scales). The main factors in the benefit-risk assessment for patients were quality of life (95.1%), disease activity (87.5%), and presence of comorbidities (84.5%). The main factors for physicians were presence of comorbidities (99.3%), disease activity (97.9%), prior failure to biologics or small molecules (96.6%). Disease duration, family history of IBD, administration interval, therapy duration, and administration route had a limited role for both physicians and patients. Based on patients' and physicians' opinions, the risk of serious infections (90.5% and 98.6%), malignancies (90.5% and 100.0%), cardiovascular events (88.8% and 98.6%), death (86.4% and 91.8%), relapse (86.1% and 94.5%), all infections (86.1% and 100.0%), surgery (83.1% and 93.1%), and hospitalization (76.6% and 88.4%) should be included in the benefit-risk assessment. The risk percentages considered acceptable by patients and physicians are reported in Figures 1 and 2. Infliximab was the most effective drug for physicians in inducing and maintaining disease remission in both Crohn's disease and ulcerative colitis, while ustekinumab and vedolizumab were equally considered the safest drugs. Conclusion: Physicians and patients have different priorities in evaluating the benefit-risk balance of a new therapy. Treatment decisions should be discussed and shared with patients.